89.5k views
4 votes
C(n)=4/9(-3)^n-1. WHATS THE 3rd TERM? Please help I can’t get this done

1 Answer

3 votes

Answer:

Third term=4

Explanation:

Given:

C(n)=4/9(-3)^n-1

Find the third term

Let n=3

Substitute n=3 into the equation

C(n)=4/9(-3)^n-1

C(3)=4/9(-3)^3-1

Step 1: evaluate the power 3-1

C(3) = 4/9(-3)^2

Step 2: evaluate (-3)^2

C(3) = 4/9(9)

It can be rewritten as

C(3) = 4/9*9

9 numerator will strike 9 denominator out leaving 4

C(3)=4

Therefore, the third term=4

C(3)=4

User Diego Antunes
by
5.4k points